Epidermal growth factor receptor inhibition in lung cancer: the evolving role of individualized therapy - Gazdar, Adi F. (2010)
Non-small cell lung cancer (NSCLC) is the major cause of cancer-related deaths in the USA and worldwide. Most patients present with advanced disease, and treatment options for these patients are generally limited to platinum-based chemotherapy and a few targeted therapies. Targeted agents currently in use for NSCLC inhibit oncogenic receptor tyrosine kinase pathways, such as the epidermal growth factor receptor (EGFR) pathway. While current EGFR-targeted agents, including erlotinib and gefitinib, may result in dramatic responses, they demonstrate efficacy in only a fraction of patients, and resistance to these agents frequently develops. In order to select patients most likely to benefit from blockade of EGFR pathways, investigators have focused on identifying molecular correlates of response to anti-EGFR therapy. New strategies to minimize the risk of resistance to EGFR inhibition have been employed in the development of next-generation EGFR tyrosine kinase inhibitors, such as PF00299804 and BIBW 2992; these include irreversibility of target binding, inhibition of multiple EGFR family receptors, and/or simultaneous inhibition of EGFR and other oncogenic pathways.